Insight Into the Beneficial Role of Lactiplantibacillus plantarum Supernatant Against Bacterial Infections, Oxidative Stress, and Wound Healing in A549 Cells and BALB/c Mice - Ashish Kumar Dubey; Ashish Kumar Dubey; Mansi Podia; Priyanka; Priyanka; Sachin Raut; Sachin Raut; Sanpreet Singh; Anil Kumar Pinnaka; Anil Kumar Pinnaka; Neeraj Khatri; Neeraj Khatri (Frontiers Media S.A., 2021)
Lactiplantibacillus plantarum MTCC 2621 is a well-characterized probiotic strain and is reported to possess many health benefits. However, the wound healing potential of this probiotic is yet to be explored. Here, we have assessed the antibacterial, antioxidant, and wound healing activities of cell-free supernatant of Lactiplantibacillus plantarum MTCC 2621 (Lp2621). Lp2621 exhibited excellent antibacterial activity against the indicator bacteria in the agar well diffusion assay. Lp2621 did not show any hemolytic activity. The safety of Lp2621 gel was established using the skin irritation assay in BALB/c mice, and no dermal reactions were observed. The supernatant showed 60-100% protection of A549 cells against H2O2-induced stress. In the scratch assay, Lp2621 accelerated wound healing after 24 h of treatment. The percent wound healing was significantly higher in cells treated with Lp2621 at 18-24 h posttreatment. In an excision wound healing in mice, topical application of Lp2621 gel showed faster healing than the vehicle- and betadine-treated groups. Similar wound healing activity was observed in wounds infected with Staphylococcus aureus. Histological examination revealed better wound healing in Lp2621-treated mice. Topical treatment of the wounds with Lp2621 gel resulted in the upregulation of pro-inflammatory cytokine IL-6 in the early phase of wound healing and enhanced IL-10 expression in the later phase. These findings unveil a protective role of Lp2621 against bacterial infection, oxidative stress, and wound healing.